2011
DOI: 10.1080/00103624.2011.558963
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Uptake of Sodium and Potassium in Broad Bean (Vicia fabaL.) under Salinity Stress

Abstract: Vicia faba L. (broad bean or faba bean), a food crop of worldwide importance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…In a work on two cultivars of broad bean, two sources of K + , i.e., KNO 3 and CH 3 COOK, were used in a nutrient solution to combat salinity. However, neither was growth improved nor the K + concentration increased in the plant tissue (Bulut et al, 2011).…”
Section: Hydroponic Studiesmentioning
confidence: 90%
“…In a work on two cultivars of broad bean, two sources of K + , i.e., KNO 3 and CH 3 COOK, were used in a nutrient solution to combat salinity. However, neither was growth improved nor the K + concentration increased in the plant tissue (Bulut et al, 2011).…”
Section: Hydroponic Studiesmentioning
confidence: 90%
“…Excess soil salinity affects both growth and nitrogen fixation in faba bean plants, which are considered moderately tolerant of soil salinity ( Bulut et al, 2011 ). Katerji et al (2011) report a yield reduction in faba bean at soil salinity levels of ≥6.5 dS m -1 .…”
Section: Adaptability Of Faba Bean To Abiotic Stressmentioning
confidence: 99%
“…Experimental studies related to nutrient-salt interactions, and plant growth and quality were completed for several plants, including: horticultural crops (Prazeres et al 2013;Saykhul et al 2013), leguminous crops (Correia et al 2010;Bulut et al 2011) and grasses (Morshedi and Farahbakhish 2012). It was shown that yield response to salinity tolerance is not always a constant as the model of Maas and Hoffman (1977) suggests, but fertilization increases tolerance to salinity (salinity threshold value); however, at high salinity levels, the osmotic effect is more pronounced and enhanced fertilization may provoke a negative effect on crop yield .…”
Section: Introductionmentioning
confidence: 99%